2018
DOI: 10.5455/ajrms.20180109094114
|View full text |Cite
|
Sign up to set email alerts
|

Acute and sub-chronic oral toxicity studies on the methanol leaf extract of Gnetum africanum Welw in wistar rats.

Abstract: Aim: Acute and subchronic toxicity studies were performed on Gnetum africanum Welw leaves using well-established guidelines and methods. In spite of its use as a herbal remedy, there is a dearth of data on toxicity studies of the plant extract. Method: Gnetum africanum leaves were identified by a plant taxonomist, air-dried, pulverized, and extracted with 80% methanol for 48 hours in July 2015. The extract was concentrated in-vacuo and stored as Gnetum africanum extract (GAE) at 4°C. Thirty-five male albino ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
(23 reference statements)
2
5
0
Order By: Relevance
“…Various parameters of the clinical findings are illustrated in Table 5 . The renal, liver function tests and various biochemical parameters showed slight variation as compared to the control group and the overall results were found in line with the already reported literature [ 28 ]. No mortality rate was observed during the study, there was neither significant nor gross histopathological lesion in the heart, lung, liver, kidney and intestine tissues of Wistar rats ( Fig 7 ).…”
Section: Resultssupporting
confidence: 91%
“…Various parameters of the clinical findings are illustrated in Table 5 . The renal, liver function tests and various biochemical parameters showed slight variation as compared to the control group and the overall results were found in line with the already reported literature [ 28 ]. No mortality rate was observed during the study, there was neither significant nor gross histopathological lesion in the heart, lung, liver, kidney and intestine tissues of Wistar rats ( Fig 7 ).…”
Section: Resultssupporting
confidence: 91%
“…This result suggests that this extract, administered orally to rats for 90 days, does not have a toxic effect on the heart. The effects of ETASg on the histology of heart of the rats tested in our study were similar to the results of studies by Udeh et al (2018). These authors showed that the histological test of the heart of the rats tested with the methanolic extract of the leaves of Gnetum africanum Welw (Gnetaceae) at the doses of 10, 20 and 40 mg/kg b. w. has normal heart tissue after 90 days of experimentation.…”
Section: Discussionsupporting
confidence: 90%
“…Studies on Gnetum africanum showed that the crude extract caused significant reductions in blood glucose levels of diabetic rats [10] and reversed alloxan-induced destruction of the pancreatic islet cells [11,31]. Its safety has also been established in Wistar rats following acute and sub-chronic studies (12). Like other flavanols, (-)-epicatechin are known to prevents oxidation and covalentmodifications caused by free radicals in proteins,improve the plasma insulin and antioxidant levels in diabetic rats and alsosignificantly decreased the levels of blood glucose, HbA1c [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…It is relevant in ethnomedicine in Nigeria for the treatment of diabetes, piles, high blood pressure, sore throats and enlarged spleen [8,9]. Recent studies have established antidiabetic and antidyslipidaemic as well as protective effects of G. africanum on rat pancreatic islets [10][11][12]. However, no active principle has hitherto been isolated from the plant with these bioactivities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation